O042 Sleep's relationship with mood and loneliness among working women during New Zealand's COVID-19 lockdown. (9th November 2022) - Helles, M; Fletcher, R; Münch, M; Gibson, R
Abstract: Background: The COVID-19 lockdown enforced unique limitations on social and working life. Changes to sleep and mood have been reported with mixed results, possibly related to measuring such outcomes between populations and social contexts. This study examined mood's relationship to sleep among a group considered to experience increased stressors during lockdown – working women. Method: Data from 498 women who were working prior to lockdown was drawn from an online survey launched during New Zealand's 2020 lockdown. Participants mean age was 44.6 years (SD= 12.6), 63.5% had been working fulltime, mean Pittsburgh Sleep Quality Index (PSQI) score was 6.6 (SD 3.6) with 54.8% scoring >5. Confirmatory Factor Analyses were conducted on the PSQI as well as measures of mood (Hospital Anxiety and Depression Scale), and loneliness (Gierveld loneliness scale). Structural Equation Modelling assessed the relationship between anxiety, depression, and loneliness with sleep status (using a higher order model for PSQI). Findings: Significant (p<0.001) positive relationships were identified between all predictors with global PSQI: Anxiety (b = .33), Depression (b = .28), Social Loneliness (b = .17) and Emotional Loneliness (b = .11). Psychometric analyses concerning the measures and their underlying constructs will also be presented. Conclusions: These findings provide deeper insight into measuring and understanding sleep and wellbeing during lockdown. Increased sleep disturbance was significantly associated with indicators of poorer mood and loneliness, highlighting some of the impacts that situations such as lockdown has among female workers.